The Verbatim Formula: caring for care leavers in the neoliberal university. Issue 3 (3rd July 2019) - Inchley, Maggie; Dar, Sadhvi; Pujara, Susmita; Baker, Sylvan
ABSTRACT: British universities have historically excluded sections of society from entering and from participating in decision-making. The neoliberal university has entrenched these inequalities in insidious ways that are resistant to change. By drawing on critical feminisms, we delineate a politics of careful solidarity that can mitigate the erasure of marginalised young people in university governance structures. We outline a participatory methodology that uses arts-based evaluation to provide channels for democratic discussion and listening. Our methodology centres the voices of young people with an experience of the care system – a cohort who are heavily excluded, and whose knowledge is stigmatised.